2020
DOI: 10.1097/md.0000000000023141
|View full text |Cite
|
Sign up to set email alerts
|

Serum essential trace elements and toxic metals in Chinese diabetic retinopathy patients

Abstract: Trace elements are essential for the proper functioning of proteins, enzymes, and transcriptional factors. However, toxic metals will compete with essential trace elements, and damage enzymatic activities and various physiological functions. We aimed to investigate the status of serum essential trace elements and toxic metals in Chinese diabetic retinopathy (DR) patients, and to analyze their associations. This retrospective study included 33 normal subjects (normal group), 44 type 2 diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Handan et al found that Se exerts a protective effect on retinal pigment epithelium (ARPE-19) and primary human retinal microvascular endothelial (ACBRI 181) cells against high glucose (HG)-induced oxidative stress and apoptosis 21 . A previous retrospective study found that blood Cd levels were higher in the DR group than in the DM group 22 . These findings are inconsistent with our results, perhaps due to different populations, races, disease states, and health conditions that affect the absorption, transport, and metabolism of Se and Cd in the body, affecting the association between Se and Cd and the disease.…”
Section: Discussionmentioning
confidence: 85%
“…Handan et al found that Se exerts a protective effect on retinal pigment epithelium (ARPE-19) and primary human retinal microvascular endothelial (ACBRI 181) cells against high glucose (HG)-induced oxidative stress and apoptosis 21 . A previous retrospective study found that blood Cd levels were higher in the DR group than in the DM group 22 . These findings are inconsistent with our results, perhaps due to different populations, races, disease states, and health conditions that affect the absorption, transport, and metabolism of Se and Cd in the body, affecting the association between Se and Cd and the disease.…”
Section: Discussionmentioning
confidence: 85%
“…One study from China that included 135 patients investigated the role of serum trace elements and heavy metal levels in diabetic retinopathy [23]. The study found that the serum concentrations of manganese (Mn) and zinc (Zn) were significantly lower in the diabetic retinopathy group, while cadmium (Cd) and cesium (Cs) levels were higher [23]. However, only selenium levels were measured in the study and not other trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…It is a source of mitochondrial reactive oxygen species (ROS) in DR, and it can disrupt glucose uptake and regulation (12,29). Some previous studies indicated that accumulated cadmium was highly associated with the presence of DR (13,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…It is a source of mitochondrial reactive oxygen species (ROS) in DR, and it can disrupt pancreatic b cells (12). One previous study had shown that the serum levels of cadmium was significantly higher in the DR groups (13). Another study was suggested that high cadmium levels decrease the formation of calcitriol (active vitamin D) in blood, thereby decreasing calcium absorption (14).…”
mentioning
confidence: 99%